2008
DOI: 10.1016/j.mee.2007.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Novel microsystems for concentration gradient generation through computer optimization with validation using optical instrumentation

Abstract: Novel microfluidic resistive network designs have been evaluated theoretically and experimentally. Such networks are an important component of microreactor technology and are used in analytical and biomedical applications for precisely controlled and evenly stepped dilution. A detailed model and a simplification algorithm have been devised for these networks. Their combination produces novel simplified network designs that exhibit less hierarchical branching over existing network designs. Rapid prediction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…b) Hydrophilic Drug A and Drug B dilutions are performed within a microfluidic device. [Chip (shown) fabricated by 3D printing (unpublished data by the authors) for Worldcare Technologies Inc, using the design from, [245,246] )] c) The candidate drug(s) flow into a device with droplet forming junctions which can generate triple emulsions (i.e., droplet incubator) at the outlet. d) Droplet incubators collected into a 24-well plate for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…b) Hydrophilic Drug A and Drug B dilutions are performed within a microfluidic device. [Chip (shown) fabricated by 3D printing (unpublished data by the authors) for Worldcare Technologies Inc, using the design from, [245,246] )] c) The candidate drug(s) flow into a device with droplet forming junctions which can generate triple emulsions (i.e., droplet incubator) at the outlet. d) Droplet incubators collected into a 24-well plate for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Alternations were put forward to circumvent these problems. [78][79][80][81] For example, Yusuf et al 82 divided the horizontal channel into two parts at the third stage and added a branch at either part, as shown in Fig. 2(b) and (d).…”
Section: Concentration Gradient Generation Methods Based On Microfluimentioning
confidence: 99%
“…The microreactor design has been fabricated according to the layout and channel geometry detailed previously (Abdulla Yusuf et al 2008), and shown in Fig. 1.…”
Section: Fabrication Of the Microreactormentioning
confidence: 99%
“…The linearity of the outlet concentration profile is based on the fact that the hydrodynamic resistances of the joint channels (horizontal channels) R H are negligible with respect to those of the serpentines (vertical channels) R v . This was achieved by defining a criteria limit of R v /R H *100:1 (Dertinger et al 2001;Abdulla Yusuf et al 2008). Scaling down the design is therefore possible, provided that the criteria limit has been met; a design with the lowest fabrication limit of the CNC machine (cross-sectional area A = 100 9 100 lm 2 for the serpentines) was initially fabricated.…”
Section: Fabrication Of the Microreactormentioning
confidence: 99%
See 1 more Smart Citation